Evaluation of a Retinol Nanoemulsion Gel Enriched with Black Seed and Rosehip Oils for Acne Management - Reddy, Aishwarya; Ravichandran, Ashwin; Magham, Sai Varshini (Drug Research, 2025)
Acne vulgaris, a prevalent inflammatory skin condition, impacts both appearance and quality of life, especially in adolescents. This study explores a novel treatment combining black seed oil, rosehip oil, and retinol within a nanoemulsion to improve therapeutic efficacy, drug delivery, and patient compliance while minimizing side effects.A nanoemulsion incorporating black seed oil, rosehip oil, and retinol was developed and characterized. Antimicrobial activity was evaluated via in vitro assays, while anti-inflammatory potential was assessed using standard models. HaCaT cell lines were used to determine cell viability. The formulation’s performance was compared with commercially available Retino AC gel, focusing on stability, penetration, and overall effectiveness.The nanoemulsion showed strong antimicrobial effects against acne-related microbes, reduced inflammatory markers, and preserved high cell viability, confirming its biocompatibility. The combined action of black seed oil’s anti-inflammatory and antioxidant properties, rosehip oil’s sebum-regulating effects, and retinol’s ability to promote cell turnover enhanced overall therapeutic outcomes. Compared to Retino AC gel, the nanoemulsion demonstrated superior efficacy, stability, and potential for better patient adherence.This study presents a synergistic, nature-based, and nano-enabled approach to treating acne and scars. The nanoemulsion offers a promising alternative to conventional therapies by improving effectiveness and safety. These results support further clinical development and highlight the potential of combining natural ingredients with advanced delivery systems for managing acne vulgaris.
Keywords: acne vulgaris; nanoemulsion gel; retinol; black seed oil; rose hip oil